Abuse of Dominance and Antitrust Enforcement in the German Electricity Market - Tomaso Duso; Florian Szücs; Veit Böckers (Center for Economic Studies and ifo Institute (CESifo), 2017)
In 2008, the European Commission investigated E.ON, a large and vertically integrated electricity company, for the alleged abuse of a joint dominant position by strategically withholding generation capacity. The case was settled after E.ON agreed to divest 5,000 MW generation capacity as well as its extra-high voltage network. We analyze the effect of these divestitures on German wholesale electricity prices. Our identification strategy is based on the observation that energy suppliers have more market power during peak periods when demand is high. Therefore, a decrease in market power should lead to convergence between peak and off-peak prices. Using daily electricity prices for the 2006 - 2012 period and controlling for cost and demand drivers, we find economically and statistically significant convergence effects after the implementation of the Commission's decision. Furthermore, the price reductions appear to be mostly due to the divestiture of gas and coal plants, which is consistent with merit-order considerations. Placebo regressions support a causal interpretation of our results.
Keywords: K21; L41; L94; 330; electricity; wholesale prices; EU Commission; abuse of dominance; ex post evaluation; E.ON